Associational protection of urban ash trees treated with systemic insecticides against emerald ash borer - Mwangola, Dorah M.; Kees, Aubree M.; Grosman, Donald M.; Norris, Kari E.; Maddox, Mitchell P.; Aukema, Brian H. (Frontiers in Insect Science, 2023)
Emerald ash borer (EAB), Agrilus plannipenis Fairmaire, is an invasive insect accidentally introduced to North America from Asia that attacks and kills ash trees (Fraxinus spp.). A common control strategy in urban centers has been the injection of systemic insecticides into mature trees, which can be costly at large scales. This study investigated whether treating a subset of a susceptible urban ash population could confer associational protection to untreated trees; i.e. improving or maintaining crown health of the latter. We selected approximately 100 mature ash trees along city streets in each of 12 sites in central and southeastern Minnesota in 2017. Each site had low but growing infestations of EAB such that canopy decline was not yet widespread. We treated 50% of trees with emamectin benzoate in eight sites and 50% of trees in four sites with azadirachtin in site-wide spatial gradients, such that the remaining 50% of trees at all sites were left untreated. Crown health of all trees was monitored for five years (2017 to 2021). Across all sites, we noted an overall maintenance or increase in crown health of both treated and untreated trees, while groups of untreated reference trees approximately three km distant from each site to monitor general tree health and EAB pressure declined quickly. These results suggested that protective benefits were conferred by treated trees to untreated trees within sites. Quantifying the spatial scale of canopy preservation of untreated trees within sites proved challenging due to the lack of variation in crown condition between treated and untreated trees. In two of the twelve sites treated with emamectin benzoate, we noted statistical evidence of improvements in crown condition of untreated trees when located within 100m of treated trees. Treating a subset of a susceptible ash population may aid in preserving untreated trees and provides a basis for developing a more cost-effective and environmentally favorable treatment regimen against EAB.